Victor Turners Theory of Ritual - Segal, Robert Alan (Zygon, 1983)
Abstract. Like Clifford Geertz and Mary Douglas, Victor Turner considers religion the key to culture and ritual the key to religion. Like them as well, he interprets religion the way believers purportedly do: as beliefs, as beliefs about the cosmos, yet as cosmic beliefs compatible with modern science. Ritual serves to express those cosmic beliefs–not for the scientific purpose of explaining or controlling the cosmos but for the existential purpose of giving human beings a place in it. Ritual serves simultaneously to express beliefs about society–not only for the functionalist purpose of keeping human beings in their social place but also for the existential purpose of giving them a social place.